Analysis of Cycloidal Pinwheel Drive Lubrication Characteristic based on Fractal Rough Surface - Fushuai Zhang; Ju Han; Muai Wang; Tianyou Bai (Jixie chuandong)
Combining the surface topography model of pin tooth and cycloid tooth constructed by fractal theory，and the proposed film thickness formula of line contact lubricated with grease based on the Herschel-Bulkley model，the minimum film thickness in the meshing process of modified pin tooth and cycloid tooth is investigated. The position of minimum film thickness during meshing process is determined. The influence of the macroscopical design parameters and modification parameters of cycloid tooth on the minimum film thickness and lubrication state is analyzed. Using the basic parameters determined by empirical formula and elastohydrodynamic lubrication numerical calculation，the lubrication characteristics of cycloidal pinwheel drive is studied.